EVALUASI KONDISI OPERASI STERILISASI TERHADAP KEHILANGAN MINYAK PADA PRODUKSI MINYAK SAWIT MENTAH - Aldi, Akri; Youfa, Rita (Politeknik ATI Padang, 2020)
The sterilization process in the boiling of fresh fruit bunches (FFB) of oil palm is a critical stage in crude palm oil (CPO) production. The primary goals of this process are to soften the bunches, deactivate destructive enzymes, and facilitate the separation of the fruitlets from the bunch. However, deviations in pressure and boiling duration from the standard can lead to oil losses, where oil is carried away by the condensate. This study analyzes the impact of pressure and boiling conditions on oil losses during the three peaks of sterilization. Results indicate that increased pressure above the standard, particularly during the first and second peaks, significantly contributes to higher oil losses. Additional factors influencing these losses include the physical condition of the fruit, steam pressure fluctuations, and the quality and stability of the steam used. At the third peak, despite reaching a pressure of 2.8 bar, technical issues such as sterilizer leaks and unstable steam supply also led to variations in oil losses. In conclusion, minimizing oil losses requires strict control over pressure, the physical condition of the fruit, and steam quality during the sterilization process.